2017
DOI: 10.1002/cam4.1023
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy against metastatic bladder cancer by combined administration of granulocyte macrophage‐colony stimulating factor and interleukin‐2 surface modified MB49 bladder cancer stem cells vaccine

Abstract: In previous studies, it has been shown that the granulocyte macrophage‐colony stimulating factor (GM‐CSF) or interleukin‐2 (IL‐2) surface modified MB49 bladder cancer stem cells (MCSCs) vaccine could induce a specific antitumor immunity and against bladder cancer in mice model respectively. However, whether combined administration of GM‐CSF and IL‐2 could produce specific immune responses to cancer stem cells (CSCs) was uncertain. MCSCs were established and characterized. GM‐CSF and IL‐2 MCSCs vaccines were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Our previous study demonstrated that the GM-CSF-modified MCSCs vaccine could significantly promote the uptake of tumor-associated antigens by the immune system and enhance the immunogenicity of tumor cells, tumor-specific CTL activity, and in vivo antitumor responses. [6][7][8] The results of our study also showed that more mature DCs were detected in the spleen of mice treated with the MCSCs vaccine. However, although this vaccination approach induced unprecedentedly strong CD8 1 T-cell responses and CD4 1 T-cell responses, this effect was usually restricted to the early stages of tumor growth.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our previous study demonstrated that the GM-CSF-modified MCSCs vaccine could significantly promote the uptake of tumor-associated antigens by the immune system and enhance the immunogenicity of tumor cells, tumor-specific CTL activity, and in vivo antitumor responses. [6][7][8] The results of our study also showed that more mature DCs were detected in the spleen of mice treated with the MCSCs vaccine. However, although this vaccination approach induced unprecedentedly strong CD8 1 T-cell responses and CD4 1 T-cell responses, this effect was usually restricted to the early stages of tumor growth.…”
Section: Discussionsupporting
confidence: 70%
“…Through our protein–anchor platform, the proposed MCSCs vaccine not only contained all of the tumor‐associated antigens but also maintained the activity of cytokines to enhance the immunogenicity of the vaccine. Our previous study demonstrated that the GM‐CSF‐modified MCSCs vaccine could significantly promote the uptake of tumor‐associated antigens by the immune system and enhance the immunogenicity of tumor cells, tumor‐specific CTL activity, and in vivo antitumor responses . The results of our study also showed that more mature DCs were detected in the spleen of mice treated with the MCSCs vaccine.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Following GVAX inoculation, sustained local release of GM-CSF significantly increased levels of M1 macrophages, dendritic cell populations, and CD8 + T cells, exerting antitumor immunity effects [ 170 ]. In addition, the IL-2 vaccine can also induce specific antitumor immunity in mice, and the combination of GVAX and IL-2 vaccine was noted to have better antitumor effects than the single treatment [ 171 ]. These results suggest that GVAX can induce strong tumor immunity and can be used in tumor immunotherapy.…”
Section: Therapeutic Strategies Targeting Cscs and Tamsmentioning
confidence: 99%